Developing a generic review framework to assure capstone quality. Issue 4 (7th June 2018) - Hammer, Sara; Abawi, Lindy; Gibbings, Peter; Jones, Hazel; Redmond, Petrea; Shams, Syed
ABSTRACT: Within the higher education context, capstone units can be viewed as a significant means of assuring intended learning outcomes for programmes. They provide students with the opportunity to consolidate and apply prior and new disciplinary learning, as well as employability skills and graduate attributes. This paper describes the first stage of an initiative in a regional, Australian university to develop a capstone quality review framework that can be applied across disciplines. A deductive, thematic analysis of relevant literature, guides and institutional strategic documents using a constant comparison method was used to develop a collectively agreed upon set of capstone quality domains and related criteria. These would enable reviewers to assess whether capstone curricula were fit-for-purpose. Capstone domains and criteria were validated and revised using a multi-stage, moderated review of 10 capstone units. This validation process affirmed that to avoid issues with reviewer inter-rater reliability, future use of our framework should emphasise calibrating reviewer interpretation to ensure greater levels of shared understanding of underlying concepts. It further suggested the desirability of incorporating aspects of teacher self-assessment, teacher feedback and student results. Provided these findings are accounted for, we conclude that the proposed capstone review domains and criteria could be used for quality review and enhancement, or capstone benchmarking processes, regardless of discipline area.